African Handbook of Climate Change Adaptation 2021
DOI: 10.1007/978-3-030-45106-6_17
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Climate-Smart Agriculture Technologies in Maize Production in Smallholder Farming Systems

Abstract: Smallholder farmers who grow the staple maize crop rely mainly on rain-fed agricultural production, and yields are estimated to have decreased by over 50% largely due to climate change. Climate-smart agriculture (CSA) technologies, as adaptive strategies, are thus increasingly being promoted to overcome problems of declining agricultural productivity and reduced technical efficiency. This study analyzed profitability and profit efficiency in maize (Zea mays) production as a result of CSA technology adoption us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Research on the effect of adopting SAPs on the productivity and efficiency of smallholder agriculture is growing (Adimassu et al 2017;Ekman 2021;McCarthy et al 2021;Mujeyi & Mudhara 2021;Pangapanga-Phiri & Mungatana 2021). Nonetheless, the evidence remains inconclusive.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on the effect of adopting SAPs on the productivity and efficiency of smallholder agriculture is growing (Adimassu et al 2017;Ekman 2021;McCarthy et al 2021;Mujeyi & Mudhara 2021;Pangapanga-Phiri & Mungatana 2021). Nonetheless, the evidence remains inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the evidence remains inconclusive. Pangapanga-Phiri and Mungatana (2021), for instance, noted an 18% improvement in technical efficiency for farmers adopting organic manure; Ekman (2021) found that intercropping and organic manure improve productivity by 59% and 54% respectively, whilst Mujeyi and Mudhara (2021) noted that the adoption of mulching, organic manure, crop rotation and intercropping improved profit efficiency. In contrast, Adimassu et al (2017) found that the adoption of SAPs, including stone bunds, significantly reduced maize yields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation